Peran Karakteristik Individu pada Hubungan Karakteristik Pekerjaan terhadap Kepuasan Kerja Freelancer di Kota Denpasar - Widya Goca, I Gusti Putu Agung; Ovy Dwijayanthi, Anak Agung Istri Agung; Amanda Putri, Komang Ayu Ratih (BUDGETING : Journal of Business, Management and Accounting, 2024)
Job satisfaction is a key element for a worker, including freelancers who work independently. High job satisfaction is usually able to improve workers' work results, where if the level of satisfaction is higher it tends to increase work enthusiasm, being on time at work and enjoying the work being done (Sofia et al., 2019). The expected aim of this research is to explore the factors that have an impact on the level of job satisfaction felt by a freelancer. Apart from that, the aim is to assess the significant influence of individual and job characteristics on job satisfaction, as well as to identify the mediating role of individual characteristics in relation to freelancer job satisfaction in Denpasar City. The method used by the author in this research is to use quantitative data supported by analysis techniques, namely Structural Euquation Modeling (SEM) using the Partial Least Square (PLS) approach. To obtain the sample, the author used a purposive random sampling method with a sample of 116 freelancers in Denpasar City. The response rate from the research survey was 96% with 116 respondents filling out the questionnaire. The findings from the research confirm that job attributes have a meaningful and beneficial impact on the level of job satisfaction, while job attributes also show a positive and significant influence on individual attributes. On the other hand, individual attributes also have a significant and beneficial impact on job satisfaction. Additionally, it was revealed that individual attributes play a partial mediating role on the relationship between job attributes and job satisfaction. Keywords: Individual Characteristics, Job Characteristics and Job Satisfaction